Strategi Mitigasi Risiko pada Produksi Ikan Tuna Menggunakan Metode House of Risk dan Fuzzy - Edy Fradinata; Didi Asmadi; Ammariza Ammariza (Jurnal Serambi Engineering, 2022)
Risk is a threat that can disrupt activities or stop the production process. PT.YPT is one of the business entities engaged in the processing of tuna, especially tuna. PT.YPT itself has produced a lot of tuna which cannot be avoided, so risk mitigation is needed. The purpose of this research is to provide risk mitigation from priority risk sources that occur in tuna production activities using the House of Risk (HOR) approach and Fuzzy Logic. Data was collected by means of field observations and literature studies as preliminary research, after which the authors also conducted interviews, brainstorming and distributing questionnaires to internal companies. It can be seen that the risks that can occur in production activities are 23 risk events and 22 risk causes of which 3 risk causes have the highest percentage, namely unskilled operators (A5), less than optimal employee performance (A17) and corrosion of tools (A21). . With the Mamdani fuzzy logic approach that forms 124 IF-THEN rules, it can be seen that the three risks can be solved easily. Mitigation design is carried out to overcome these three risks by making preventive actions as many as 14 mitigation alternatives based on literacy studies and the results of discussions with the company which will be designed in the form of a traceability chart.